2023
DOI: 10.1108/md-05-2022-0600
|View full text |Cite
|
Sign up to set email alerts
|

Configurations of innovation performance in foreign owned subsidiaries: focusing on organizational agility and digitalization

Abstract: PurposeThe authors investigate conditions that drive innovation performance in foreign-owned subsidiaries. The authors study five variables affecting innovation performance: organizational agility and digital capabilities as the main drivers and competencies and embeddedness in internal and external networks as complementary antecedents of innovation.Design/methodology/approachThe authors draw on the neo-configurational perspective and apply fuzzy set qualitative comparative analysis (fsQCA) to empirically tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Organizational agility, as a dynamic capability, explains how a firm reconfigures its resources to gain market competitiveness through various measures (e.g., innovation). Dahms et al (2023) also reported that organizational agility is an antecedent to innovation performance in the study of foreign-owned subsidiaries. Therefore, the following hypotheses are proposed:…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 90%
“…Organizational agility, as a dynamic capability, explains how a firm reconfigures its resources to gain market competitiveness through various measures (e.g., innovation). Dahms et al (2023) also reported that organizational agility is an antecedent to innovation performance in the study of foreign-owned subsidiaries. Therefore, the following hypotheses are proposed:…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 90%
“…In today’s business, agility defines a firm ability to quickly and effectively recognize and react to challenges and opportunities (Dahms et al ., 2023). Firm agility is necessary for firms facing fluctuating environments to use production factors to achieve the objectives of the firms, employees, and shareholders (Röth et al ., 2023).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Contrarily, Marrucci et al (2023) investigate antecedents of Industry 4.0 implementation, finding that organizational agility and SF play a fundamental role. However, Dahms et al (2023) and Qin (2023) provide an integrative view of the interplay between SF and digitalization that combines these two apparently conflicting views. On the one hand, Dahms et al (2023) find that the interplay of organizational agility and digital capabilities contributes to superior innovation performance, but on the other hand, Qin (2023) empirically shows that a degree of flexibility is required for digital transformation that, in turn, increases flexibility.…”
Section: Research Articles Included In the Special Issuementioning
confidence: 99%
“…(2023) investigate antecedents of Industry 4.0 implementation, finding that organizational agility and SF play a fundamental role. However, Dahms et al. (2023) and Qin (2023) provide an integrative view of the interplay between SF and digitalization that combines these two apparently conflicting views.…”
Section: Research Articles Included In the Special Issuementioning
confidence: 99%
See 1 more Smart Citation